Some aspects of physical training for highly qualified swimmers during the tapering period - Feroyan, Eduard (Національний технічний університет "Харківський політехнічний інститут", 2025)
Changes in muscle force were measured during the tapering period in 17 elite male swimmers. The research was conducted before, during, and after a 14-day tapering period. Two types of tests were used: on land and in water using a special device to measure the maximum power output of arm muscles. The same parameter was also studied during a water test: each athlete had to swim 200 meters at a specified speed, which was 90% of their maximum. During the tapering period, no changes in acid balance were detected as a result of physical exertion, but a significant increase in movement power was observed (in both tests). Results improved by an average of 2.9% (due to increased muscle strength).
Keywords: physical training; highly qualified swimmers; tapering period; swimming; muscle strength; фізична підготовка; висококваліфіковані плавці; період звуження; плавання; сила м'язів